Tax-Induced Intra-Year Patterns in Bonds Yields. - Hochman, Shalom J; Palmon, Oded; Tang, Alex P (Journal of Finance, 1993)
The ratio of the yields on short-term tax-exempt and taxable bonds exhibits a sawtooth pattern that is consistent with th e impacts of tax deferments from dates on which interest payments are received to dates on which the resulting tax payments are paid. The effect of the tax deferment at turns of calendar years does not diff er appreciably from the effect at the turn of any other tax quarter. Investors with tax payment schedules that differ from that of the investor that is indifferent between investing in taxable and tax-exempt bonds may benefit from tax-related timing strategies for investing in these bonds. Issuers may benefit from tax-related timin g strategies for scheduling interest payments.